Analysis of the selection of antimicrobial drugs for community-acquired pneumonia by final year medical students - Deriushkin, V. G. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2021)
Currently bacterial community-acquired pneumonia (CAP) remains one of the important problems of providing medical care on an outpatient basis. Despite the high detection rate and modern methods of treatment this disease holds the first place among the causes of death in the category of infectious diseases. Knowledge about rational use of drugs is obtained in higher medical school and subsequently serves as a basis for further work of a practicing physician. Purpose of the study : to analyze the knowledge of final year medical students in the field of rational choice of antimicrobial agent (AMA) in the treatment of non-severe CAP in outpatient setting in patient without concomitant diseases and risk factors. Total 240 final year students of A.I. Yevdokimov Moscow State University of Medicine and Dentistry were offered in February-April, 2019 to indicate their preferred AMA for a young previously healthy patient with mild CAP. The study involved 178 women (74.17 %) and 62 men (25.83 %). The average age of the respondents was 24.8+3.3 years. There were 271 options for the appointment of AMA with 152 (56.1 %) given by the international nonproprietary name and 119 (43.9 %) by trade name. Remarkably, the AMAs which are recommended for the treatment of mild CAP on an outpatient basis, accounted only for 46.2 % in this study. Of particular concern is the fact that only about 40—50 % of AMA prescribing for CAP by medical graduates is in line with current clinical guidelines. The inappropriate choice of a drug in this particular situation not just increases the drug load, the cost of pharmacotherapy and the risk of side effects, but also directly affects the results of treatment. This situation emphasizes the need for a purposeful formation of a personal formulary of medicines for a graduate of a medical university, taking into account the basic principles of rational pharmacotherapy and the provisions of clinical guidelines relevant to the Russian Federation.